Implementasi Framework COBIT 2019 pada Tata Kelola Teknologi Informasi di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja Kota Lhokseumawe Menggunakan CMMI - Pratama, Angga; Fhonna, Rizky Putra; Liana, Fara (Jurnal Ilmiah SINUS, 2025)
Information technology plays an important role in improving public services in the government sector, including in the Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu dan Tenaga Kerja Kota Lhokseumawe. This research aims to measure the level of capability and maturity level and provide input and suggestions for improving IT management with a focus on processes that have been produced from design factors including, APO04, APO08, BAI01, BAI02, BAI03, BAI05, BAI06, BAI07, BAI08. The method applied in the research is case analysis at DPMPTSP-NAKER Lhokseumawe City, with data collection carried out through observation, interviews, filling in design factors, determining respondents using the RACI Chart and distributing questionnaires. Next, the data was analyzed with reference to COBIT 2019. Based on the research results, it was found that the APO04 process objective is at level 1, APO08 is at level 3, BAI01 is at level 1, BAI02 is at level 2, BAI03 is at level 1, BAI05 is  at level 1, BAI06  is at level 1, BAI07 is at level 1, BAI08 is at level 1. Capability can be improved by carrying out activities that have not been carried out by the agency until it reaches fully achieved status at each level.